Bioanalytical evaluation of pha co-polymer produced by Massilia Spp isolated from Rhizosphere soil - Priyanka Naik; Vaijayanti Ranade (International Journal of Pharma and Bio Sciences, 2020)
Polyhydroxyalkanotes are naturally occurring biodegradable polymers. The aim of the present study was to optimize and characterize PHA extracted from a rhizosphere soil isolate. 16S rRNA sequencing revealed that isolate belongs to the genus Massilia. Confocal laser scanning microscopy revealed the presence of bright orange colored fluorescent granules when grown under nitrogen limiting conditions and stained with Nile red dye. Present isolate was known to produce highest amount of PHA when supplemented with maltose as a carbon source and NH4HPO4 as a nitrogen source. After optimization, isolate produced 2.0g/l of PHA. FTIR spectrum of PHA revealed the presence of C=O, -OH and C-O bonding. Td of extracted polymer was found to be at 2810C. NMR and GC-MS spectrum revealed that it is a co-polymer of 3-hydroxybutyric acid (3HB) and 9, 19-dihydroxy octadecanoic acid (HOD).